PERLINDUNGAN HUKUM BAGI DOSEN SEBAGAI TENAGA PENDIDIK UNTUK MEMPEROLEH HAK KETENAGAKERJAANNYA - Ilmal Yaqin (Dialogia Iuridica, 2017)
Legal protection for all workers/employees, especially for educators who work on the foundation, is absolutely necessary, since there are still many cases involving the university and the foundation. These problems still continue to haunt educators, so it needs concerted effort to minimize existing problems. Although there are regulations governing the relations between workers/employees with employers, but in a practical level is still not fully implemented. It is associated with several problems, one of which is the position of educators at the level of sub-ordinate more than the foundation. The phenomenon can’t be happen when educators take the advantage of legal protection that already regulated by legislation. This study will elaborate on legal protection for the workers, especially for educators. The research method is a normative juridical approach using approach legislation. The results are legal protections for educators stipulated in Law No. 21 Year 2000 on the labor Unions, in particular regarding the purpose of the establishment of labor unions. In addition, Law No. 13 of 2003 on Employment already protect workers/employees, including educators, namely through union/employee